Assessing the contribution of immigrants to Canada's nursing and health care support occupations: a multi-scalar analysis - Rafael Harun; Margaret Walton-Roberts (BMC, 2022)
Abstract Background The World Health Organization adopted the Global Strategy on Human Resources for Health Workforce 2030 in May 2016. It sets specific milestones for improving health workforce planning in member countries, such as developing a health workforce registry by 2020 and ensuring workforce self-sufficiency by halving dependency on foreign-trained health professionals. Canada falls short in achieving these milestones due to the absence of such a registry and a poor understanding of immigrants in the health workforce, particularly nursing and healthcare support occupations. This paper provides a multiscale (Canada, Ontario, and Ontario's Local Health Integration Networks) overview of immigrant participation in nursing and health care support occupations, discusses associated enumeration challenges, and the implications for health workforce planning focusing on immigrants. Methods Descriptive data analysis was performed on Canadian Institute for Health Information dataset for 2010 to 2020, and 2016 Canadian Census and other relevant data sources. Results The distribution of nurses in Canada, Ontario, and Ontario's Local Health Integration Networks reveal a growth in Nurse Practitioners and Registered/Licensed Practical Nurses, and contraction in the share of Registered Nurses. Immigrant entry into the profession was primarily through the practical nurse cadre. Mid-sized communities registered the highest growth in the share of internationally educated nurses. Data also pointed towards the underutilization of immigrants in regulated nursing and health occupations. Conclusion Immigrants comprise an important share of Canada's nursing and health care support workforce. Immigrant pathways for entering nursing occupations are complex and difficult to accurately enumerate. This paper recommends the creation of an integrated health workforce dataset, including information about immigrant health workers, for both effective national workforce planning and for assessing Canada's role in global health workforce distribution and utilization.